No apparent genetic bottleneck in the demographically declining European eel using molecular genetics and forward-time simulations - Pujolar, J. M.; Bevacqua, Danièle; Capoccioni, F.; Ciccotti, E.; de Leo, G.A.; Zane, L. (Conservation Genetics, 2011)
International audience The stock of the European eel is considered to be outside safe biological limits, following a dramatic demographic decline in recent decades (90–99% drop) that involves a large number of factors including overfishing, contaminants and environmental fluctuations. The aim of the present study is to estimate the effective population size of the European eel and the possible existence of a genetic bottleneck, which is expected during or after a severe demographic crash. Using a panel of 22 EST-derived microsatellite loci, we found no evidence for a genetic bottleneck in the European eel as our data showed moderate to high levels of genetic diversity, no loss of allele size range or rare alleles, and a stationary population with growth values not statistically different from zero, which is confirmed by finding comparable value of short-term and long-term effective population size. Our results suggest that the observed demographic decline in the European eel did not entail a genetic decline of the same magnitude. Forward-time simulations confirmed that large exploited marine fish populations can undergo genetic bottleneck episodes and experience a loss of genetic variability. Simulations indicated that the failure to pick up the signal of a genetic bottleneck in the European eel is not due to lack of power. Although anthropogenic factors lowered the continental stock biomass, the observation of a stable genetic effective population size suggests that the eel crash was not due to a reduction in spawning stock abundance. Alternatively, we propose that overfishing, pollution and/or parasites might have affected individual fitness and fecundity, leading to an impoverished spawning stock that may fail to produce enough good quality eggs. A reduced reproduction success due to poor quality of the spawners may be exacerbated by oceanic processes inducing changes in primary production in the Sargasso Sea and/or pathway of transport across the Atlantic Ocean leading to a higher larval mortality.